Engineering antiferroelectric nucleation in ferroelectric films with enhanced piezoelectricity. (15th May 2023) - Liu, S.Z.; Geng, W.R.; Tang, Y.L.; Zhu, Y.L.; Wang, Y.J.; Cao, Y.; Jiang, R.J.; Liu, N.; Gong, F.H.; Wang, J.H.; Lv, X.D.; Chen, S.J.; et al.
Abstract: Tailoring ferroelectric-antiferroelectric phase transitions provides strategic advantages for potential applications in digital displacement transducers and ultrathin ferroelectric capacitors. In particular, epitaxy of artificial superlattice has been widely used and proved to be capable of creating antiferroelectric-type characteristics within intrinsic ferroelectrics. Here, we have achieved dedicatedly control of ferroelectric-antiferroelectric phase transition by introducing 2 unit-cells antiferroelectric PbZrO3 layers into the intrinsic ferroelectric BiFeO3 films, with the ultrathin PbZrO3 layers acting as the structural spacer to bridge the robust nucleation of striping phase in BiFeO3 layers. Aberration-corrected scanning transmission electron microscopy characterization revealed that the BiFeO3 layers experienced a transition to the antiferroelectric-like polymorph via interface-transferred lattice distortion of alternate cation displacement, thereby forming the periodic ferroelectric-antiferroelectric nanoscale laminas. Further piezoresponse force measurements gave the direct evidences that the modulated superlattice exhibited improved piezoelectric performance compared with typical rhombohedral BiFeO3 films. This work paves the way for engineering polarity-mismatched superlattices with enhanced piezoelectric response and enriches the fundamental of structure-functionality correlations in oxide heterosystems. Graphical abstract: Image, graphical abstract